Implementasi Pasal 3 Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah di Wilayah Kelurahan Bontang Kuala Kecamatan Bontang Utara - Rina Ekawati (Jurnal Risalah Hukum, 2009)
An interesting phenomenon relates with land registration. The usual object seems used to be national land, but the recent object of land registration corresponds with water. It becomes evident at Bontang Kuala Orchard where the inhabitants build their house on the surface of the sea. Therefore, such phenomenon remains as a subject to legal review in pursuant with Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah as the legal base to regulate land registration of Indonesia.